Hot emotions in cold landscapes. Towards spatial-emotional methodologies of interest development. Why research on Arctic winter tourism can ill afford to ignore the emotion of interest. - Ekeland, Christian (UiT Norges arktiske universitet, 2016)
The papers of this thesis are not available in Munin. Paper I: Ekeland, C., Dahl, T. I.: "Hunting the light in the high Arctic. A triangulation study of interest development among English tourists on board the coastal steamer Hurtigruten." (Manuscript). Published version, with altered title, available in Tourism Culture & Communication 2016, 16(1-2):33-58. Paper II: Ekeland, C.: "High as a kite: Exploring the positive emotion of interest through extreme sporting in the Arctic". (Manuscript). Paper III: Ekeland, C.:"Hunting the light’. A study of a tourist group and its learning experiences on-board the Norwegian coastal steamer Hurtigruten". Available in Acta Agriculturae Scandinavica B 2011, 61(1):38–51. The dissertation explores tourist encounters with two Arctic winter tourism contexts in Northern Norway. Through three ethnographic fieldworks on the coastal steamer Hurtigruten, and a small peninsula of eastern Finnmark called Ekkerøy, learning experiences are scrutinized. As tourists visit a region they know relatively little about beforehand, how important is the external scaffolding of these learning experiences? Through analyses of the emotion of interest (Silvia 2006), this work offer new insights for the domain of experience economy in tourism research (Dahl 2013). A spatial-emotional methodology is introduced combining knowledge from the disciplines of psychology and anthropology. As the candidate is an anthropologist this dissertation is a contribution in the social science domain, despite its obvious reliance upon psychological theory. It is argued that emotions are constructs that includes both heterogeneous and material environments and particular subjectively experiencing bodies (Lazarus 1991). As such, traditional ethnographic approaches to the study of emotions, which mainly emphasized the exogenic (environmental) aspect of the construct of emotion, needs to be expanded to include the endogenic (embodiment, subjective experience, motivation etc.). The dissertation thus contains a multi- ...